Gestational Weight Gain among Women at Health Centers in Tehran in 2016 - Morteza Abdollahi; Saeid Safiri; Ali-Asghar Kolahi; Mohammad-Mahdi Rashidi; Farima Mohamadi; Azadeh Ashrafi; Alireza Abadi (Salāmat-i ijtimā̒ī, 2021)
Background and Objective: Inappropriate gestational weight gain (GWG) may increase risk of adverse pregnancy outcomes. To prevent these risks, determining optimal weight gain is a priority in prenatal care. The objective of this study was to determine the GWG of women referring to health centers for their prenatal care visits in Tehran in 2016.